Remembering the XXVI SISET Congress and the 50th anniversary of its foundation, 2020 - Armando Tripodi (Bleeding, Thrombosis and Vascular Biology)
SISET stands for the Italian Scientific Society for the Study of Thrombosis and Hemostasis. Founded in 1970, it currently enrolls more than 1,000 professionals across the country. Contributions by SISET scientists range from clinical to experimental investigations and are regularly published in leading international medical journals.